Beliefs and popular practice during postpartum period: integrated review of nursing productions - Kalinowski, Luísa Canestraro; Lenardt, Maria Helena; Mazza, Verônica de Azevedo; Lacerda, Maria Ribeiro; Wall, Marilene Loewen (Online Brazilian Journal of Nursing, 2011)
Problem: Science is ultimately valued while popular practice or beliefs are viewed as unfounded experience. Thus, a clash can be observed between health professionals’ scientific knowledge and cared people’s popular knowledge or beliefs. Objective: To investigate state-of-the-art nursing production on popular knowledge and beliefs typical from the postpartum period. Methodology: Integrated review of scientific nursing productions in LILACS, SciELO, BDENF databases, and CAPES theses database between 2000 and 2009. Sixteen productions were selected and analyzed. Results: Three central themes emerged: Beliefs and popular practice on puerperal care; Beliefs and popular practice on newborn care; Nursing facing beliefs and popular knowledge during postpartum period. Conclusion: It was evidenced that nursing develops qualitative research studies in order to describe beliefs and popular knowledge, pointing out the possibility to use the ethnographic method and anthropology to make such investigations feasible. It was perceived the need to understand that such knowledge is not superior or inferior to scientific knowledge and by approaching it, nurses may find the symbolic caring dimension and, thus deliver culturally congruent care.